Studi Cross Sectional: Eksplorasi Pengetahuan dan Sikap Tentang Pengelolaan Diri pada Pasien Diabetes Mellitus Tipe 2 - Sheila Anjelyn Tarigan; Victor Trismanjaya Hulu; Simanjuntak, Mafe Robbi (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
Type 2 diabetes mellitus (DM) is a chronic disease that requires active patient participation in self-management to prevent complications and maintain optimal and sustainable quality of life. This study aims to explore knowledge and attitudes about self-management in patients with type 2 DM. This study used a descriptive method with a cross-sectional approach. The study was conducted at Puskesmas Medan Johor Pangkalan Masyhur, Medan Johor Sub-district, in 2024. The study population was all type 2 DM patients aged 40 to 60 years, totalling 213 people. A sample of 102 respondents was selected using a simple random sampling technique. Data were collected using a questionnaire to assess the level of knowledge and attitude of patients with type 2 diabetes. The data obtained were then processed and analyzed descriptively to determine the frequency distribution of each variable studied. The results showed that as many as 55.9% of patients with type 2 DM had poor knowledge about self-management, and 44.1% had good knowledge. A total of 23.5% of patients with type 2 diabetes mellitus had a negative attitude, and 76.6% had a positive attitude. The conclusion is that most type 2 DM patients have poor knowledge about self-management, although the majority show a positive attitude.